Anti-solvent mixture-mediated reduction of photocurrent hysteresis in high-impurity perovskite precursor based MAPbI3 solar cells. (15th January 2021) - Li, Chung-Yu; Liao, Yin-Song; Thakur, Diksha; Chandel, Anjali; Chiang, Shou-En; Wu, Jia-Ren; Lee, Po-Han; Tsai, Chia-Lung; Yang, Chun-Chuen; Zhong, Yuan-Liang; Shen, Ji-Lin; Hsiung Chang, Sheng
Graphical abstract: Highlights: The nearly point-defect free MAPbI3 thin films can be formed by using a high-impurity precursor. The low-cost and current hysteresis-free MAPbI3 solar cells can be achieved. The dropping time of antisovlent largely influences the formation of point defects. The use of 10% dicloromethane can exclude the participation of impurities during the crystal growth process. Abstract: High-impurity precursor based CH3 NH3 PbI3 (MAPbI3 ) perovskite thin films are fabricated by using the one-step spin-coating method with an anti-solvent mixture-mediated nucleation (ASMEN) process under various dropping times. The structural, optical and excitonic properties of the resultant perovskite thin films are characterized through the X-ray diffractometer, absorbance spectrometer, photoluminescence spectrometer and Raman scattering spectrometer. The experimental results show that the dropping time and the use of 10% dicloromethane (DCM) in the ASMEN process strongly influences the formation of point defects in the resultant MAPbI3 thin film, which dominates the current-hysteresis behavior in the current density-voltage curves of solar cells. In addition, this investigation helps further understand the effects of toluene/DCM anti-solvent mixture on the formation of point defect-free MAPbI3 thin films.